Exploring Parents' Motivations for Sharenting and Consequences for Children's Well-Being - Saeid, Motevalli; Rogayah, A. Razak; Richard, Peter Bailey; Amalia, Madihie; Katayoun, Mehdinezhadnouri; Yifei, Pan (Lifescience Global, 2025)
Introduction: This literature review uses thematic analysis to identify common themes and topics in recent literature on the perceptions, attitudes, and motivations towards parents’ sharenting behavior.